El método del flúor para fechar la edad de un fósil óseo - MONTEOLIVA HERNANDEZ, MIGUEL (Ars Pharmaceutica (Internet), 1960)
A bibliographical examination of the subject is made and the conclussion is reached that there is no direct relation between the fluorine content of the bone and the time the bone has been buried. The hypothesis is put forward that the variations found by the different authors are due to the larger or smaller accumulations of fluorine in the bone during the lifetime of the animal.